Perceived efficacy of dynamic mathematical softwares of mathematics teacher trainees. - Ahmad Tarmizi, Rohani; Mohd Ayub, Ahmad Fauzi; Abu Bakar, Kamariah (2007)
The use of technology in teaching mathematics have great potentials and make significant contributions to students' learning specifically in developing skills in mathematical modeling through exploration, develop logical thinking and modify strategies and assumptions through immediate feedback, work with large sets of data and learn and memorize by manipulating graphic images. In this study an experiential learning utilizing mathematical softwares Autographs, Geometer Sketchpad and Graphing Calculator on Functions and Statistics was conducted involving students in Mathematics Teaching Methodology Course (EDU 3069). These students are trained to be mathematics teacher for the secondary level and are in their final year of study.